2019
DOI: 10.1002/elps.201800530
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic solid‐phase extraction based on carbon nanosphere@Fe3O4 for enantioselective determination of eight triazole fungicides in water samples

Abstract: In this work, a carbon nanosphere decorated by Fe3O4 nanoparticles was prepared, characterized and used as the magnetic adsorbent. Eight commonly used chiral triazole fungicides, including penconazole, uniconazole, paclobutrazol, triazolone, tebuconazole, hexaconazole, triticonazole and epoxiconazole were extracted from two environmental water samples (river water and lake water) by magnetic solid‐phase extraction, followed by the enantiomeric analysis on a Chiralpark IC column coupled with a triple quadrupole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 36 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…The results demonstrated a high extraction percentage (above 80%) of the prepared nanoabsorbent in all cases. 102 Analogously, a Zr-based magnetic metal–organic framework was developed by immobilizing UiO-66 onto Fe 3 O 4 @SiO 2 particles by a proficient single-pot solvothermal method and was used for adsorption of triclosan (TCS) and triclocarban (TCC) fungicides from water by magnetic solid phase separation. 103 It was revealed that high saturated adsorption capacities were attained for TCS and TCC removal and the process was convenient, rapid and eco-friendly and can be recycled more than 11 times.…”
Section: Functionalization Of Monps and Agricultural Waste Managementmentioning
confidence: 99%
“…The results demonstrated a high extraction percentage (above 80%) of the prepared nanoabsorbent in all cases. 102 Analogously, a Zr-based magnetic metal–organic framework was developed by immobilizing UiO-66 onto Fe 3 O 4 @SiO 2 particles by a proficient single-pot solvothermal method and was used for adsorption of triclosan (TCS) and triclocarban (TCC) fungicides from water by magnetic solid phase separation. 103 It was revealed that high saturated adsorption capacities were attained for TCS and TCC removal and the process was convenient, rapid and eco-friendly and can be recycled more than 11 times.…”
Section: Functionalization Of Monps and Agricultural Waste Managementmentioning
confidence: 99%
“…The self-assembly of Fe 3 O 4 NPs onto the surfaces of carbon nanospheres resulted in a novel magnetic adsorbent that was used in the extraction of eight triazole fungicides from environmental water samples, demonstrating a high extraction percentage (above 80%) in all cases [99]. The enantiomers of the triazole fungicides under investigation were quantified by employing chiral LC-MS/MS, while the reusability of these adsorbents was experimentally verified, since high extraction yields were retained after ten adsorptiondesorption cycles.…”
Section: Mnp-mediated Removal Of Pesticides and Antibioticsmentioning
confidence: 99%
“…They have efficient and broad-spectrum bactericidal activity and play an important role in safeguarding agriculture. 1,2 For example, myclobutanil could be used against powdery mildew affecting vegetables. 3 However, with the intemperate use of these pesticides, they may eventually enter the aqueous system, penetrate the soil and enter the groundwater.…”
Section: Introductionmentioning
confidence: 99%